2020
DOI: 10.1111/asj.13456
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Müllerian hormone is expressed and secreted by bovine oviductal and endometrial epithelial cells

Abstract: Anti-Müllerian hormone (AMH) is a member of the transforming growth factor (TGF)-β family. Preantral and small antral follicles secrete AMH in female animals (Bhide & Homburg, 2016). AMH expression is well-characterized in ovaries and plays important roles in regulating follicular development (Hernandez-Medrano, Campbell, & Webb, 2012) and inhibiting follicular atresia (Sefrioui, Madkour, Aboulmaouahib, Kaarouc, & Louanjli, 2019). Concentrations of circulating AMH can help to predict the number of high-quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Immunohistochemistry performed in the present study showed co-localization of AMHR2, HSP47, and collagen IV in the epithelial layers, thus showing epithelial cells express these proteins. These observations were supported by our recent studies of AMHR2 (Ferdousy et al, 2020a), AMH (Ferdousy et al, 2020b), and HSP47 expression in the epithelial layers of the uteri of young heifers and aged cows. In the present study, we found that AMH induces HSP47 expression in uterine epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Immunohistochemistry performed in the present study showed co-localization of AMHR2, HSP47, and collagen IV in the epithelial layers, thus showing epithelial cells express these proteins. These observations were supported by our recent studies of AMHR2 (Ferdousy et al, 2020a), AMH (Ferdousy et al, 2020b), and HSP47 expression in the epithelial layers of the uteri of young heifers and aged cows. In the present study, we found that AMH induces HSP47 expression in uterine epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
“…AMH is secreted from ovaries (Bhide & Homburg, 2016). Also endometrial epithelial cells are likely to secrete AMH into the uterine fluid at the picomolar level (Ferdousy et al, 2020b). Therefore, AMH can be transported by blood or uterine fluids to epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, within individuals, circulating AMH concentrations are stable over months or even years (Monniaux et al 2011;Evans et al 2012) because the population of growing small antral follicles, where the greatest amounts of AMH are produced, is itself quite stable (Scaramuzzi et al 2011). A degree of uncertainty has been introduced by the recent discovery that, in cattle, AMH is synthesised and secreted by epithelial cells in the oviduct and endometrium (Ferdousy et al 2020), suggesting that we can expect changes in plasma AMH concentrations as animals progress through major stages of reproductive life, such as puberty.…”
Section: Amh In the Peripheral Circulationmentioning
confidence: 99%